O uso nocivo de crack: percepções de pessoas em tratamento da dependência - Pedrosa, Sheila Mara (2016)
Drug use has always permeated human existence, being seen in certain social groups as a natural behavior since it relieves aches and pains at times and produces stimulation, and exciting and others. The cocaine is a drug which consumption has grown last years in South America, especially in Brazil, and one of its types, the crack, is the most consumed. This illicit drug, stimulates the central nervous system, often leads to dependent person to take damage in the physical, economic and social context. The isolation to which the person dependent on crack is exposed sets in extreme situation of social vulnerability that expose the consequences of a larger and broader social context that transcends the act of using the drug. The objective of this study was to understand the meanings of the harmful use of crack by people in addiction treatment. Qualitative approach of strategic social research held in a psychiatric hospital with 39 participants divided into eight focus groups. Field observation was performed with records in a field notebook. The meetings were recorded and later transcribed and analyzed through the interpretation of meanings method. Data revealed three themes that were discussed in the light of theoretical social vulnerability proposed by Robert Castel. The first, "discovery of crack and other drugs" describes the motivations to use and differentiates the trial crack with other drugs. The cited reasons were curiosity, excessive liberty of parents and relief to some disappointment in life, and also the influence of friends. The "pain of pleasure" describes the time after the trial crack when installing the dependence, leading to a cycle of short periods of attempted abstinence, relapse and incessant consumption. In his speech, although the crack has been considered the drug which, paradoxically, provides pleasure and relief to suffering leads to unbridled consumption, uncontrollable craving, loss at work, sale of goods and separation from family, conflict with drug traffickers and police, regardless in this study of purchasing power. Finally, in the "return to life" participants describe the desire for change of life after reaching an extreme situation of drug use, lack of money, conflicts in their social environment. The feeling of despair for not wanting to use the crack and not be able to do it because of addiction is also highlighted. Results showed that even before the crack addiction participants were already in a situation of social vulnerability. The approach of people in treatment for crack addiction should be done to reduce the distance between these people and the family, society and health services, which is the starting point for health professionals in the proposition of health promotion actions.